INFLUENCE OF NON-LIFE INSURANCE SECTOR CLAIMS SETTLEMENT ON THE INCREASE OF TOTAL ASSETS IN NIGERIA'S INSURANCE MARKET (2000 TO 2022) - SOLOMON DAVID PERE; JOSIAH BOLOU-OWEI EDIKE (International Studies Journal)
The study looked at the influence of non-life insurance sector claims settlement on the increase of total assets in Nigeria's insurance market from 2000 to 2022. The data set utilized for this research is secondary data, consisting of 22 years' yearly series of chosen variables from 2000 to 2022, obtained from the Central Bank of Nigeria (CBN) and the NAICOM statistics bulletin. The study used the Philip-Perron (PP) unit root test and the Ordinary least squares (multiple regressions) method with the E-view package to calculate the coefficient of the independent variable, non-life insurance claims settlement, on the total assets of the insurance industry as dependent variables. The hypothesis demonstrates that if each index for non-life insurance claims settlement is held constant, total insurance assets growth in Nigeria will increase by an intercept value of 0.0000246 basis points. Additionally, it is seen that non-life insurance claims settlement has a regression coefficient of 0.010995, which is a positive coefficient. The Adjusted Co-efficient of Determination, which was 0.050918, shows that in the model used, the independent variable. The p-value of non-life insurance claims settlement impacting total insurance asset growth in Nigeria is 0.8621, which above the level of significance of 0.05. It indicated that there was statistical insignificance. According to the study's results, non-life insurance sector claims settlement has no substantial influence on the insurance industry's overall asset growth rate.